SARS-CoV-2 and mammals: A short revision - Corrales-Aguilar, Eugenia; Murillo, Tatiana (Therya Notes, 2024)
In 2019, an outbreak of pneumonia of unknown origin was reported in China, reminiscent of the Severe Acute Respiratory Syndrome (SARS) virus outbreak during the years 2002-2003. In February 2020, the new virus was identified as a member of the Coronaviridae (CoV) family, initially named nCOV-19 and associated with the disease called COVID-19. It was later renamed SARS-CoV-2 by the international committee on taxonomy of viruses (ICTV), as it shares similarities with 6 previously known and described human coronaviruses, including SARS-CoV and MERS-CoV. Bats, reservoirs of many coronaviruses, were the first mammals presumed to be involved in the transmission cycle. The search for the natural reservoir or host of SARS-CoV-2 has focused on bats of the genus Rhinolophus (Asian horseshoe bats). However, as with other coronaviruses, intermediate hosts that have not yet been identified may be necessary for transmission to humans. The purpose of this work was to conduct a review of the current knowledge of the mammalian hosts of SARS-CoV-2 and the clinical manifestations they have presented. In addition, potential reservoirs are explored, and intermediate hosts are proposed. Finally, we list the challenges in identifying these key species in the virus transmission cycle and advocate for a One Health approach to prevent future pandemics.